2018
DOI: 10.1080/20797222.2018.1450202
|View full text |Cite
|
Sign up to set email alerts
|

Teenage Girlhood and Bodily Agency: On Power, Weight, Dys-Appearance and Eu-Appearance in a Norwegian Lifestyle Programme

Abstract: Despite the growing literature on childhood obesity and lifestyle intervention programmes focusing on weight loss, few studies have examined young persons' experiences of being identified as candidates for such programmes and of participating in them. This paper does so. Juxtaposing insights from phenomenology with an approach inspired by Foucault, the paper shows how teenage girls' bodily self-perception and bodily self-awareness are shaped in intercorporeal assemblages comprising other people and specific fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In contrast, My Vital Cycles ® built competencies using relatable science to recognize personal patterns and to determine if these fit within healthy ranges. This follows Wilding's and Griffey's call for a personalized approach [55] as well as Groven's and Zeiler's emphasis of individual agency [54].…”
Section: Theme 2 Informativementioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, My Vital Cycles ® built competencies using relatable science to recognize personal patterns and to determine if these fit within healthy ranges. This follows Wilding's and Griffey's call for a personalized approach [55] as well as Groven's and Zeiler's emphasis of individual agency [54].…”
Section: Theme 2 Informativementioning
confidence: 94%
“…An initial hesitancy to engage was replaced by easiness and confidence. Groven's and Zeiler's qualitative Norwegian study [54] similarly encountered this transformation in a girls' lifestyle program. Interviews with seven girls post-program theorized that the body is a site of self-becoming which opens up a world of meaning and understanding of the body and its capacities [54].…”
Section: Theme 1 Increasing Comfort Levelsmentioning
confidence: 98%
See 1 more Smart Citation
“…A large portion of the work in this field focuses on the stigma experienced by fat people as a result of the widespread "fear of fat" established by the dominant biomedical approach. Fat stigma can be found in family settings (Rogers, Taylor, Jafari, & Webb, 2019), dating circles, social interaction, and healthcare contexts (Taylor & Gailey, 2019), weight treatment settings (Groven & Zeller, 2018), in health circles like running (Sniezek, 2019;Inderstrodt-Stephen & Acharya, 2018). One study's participants felt this stigma so deeply that "the overwhelming majority indicated that if there were a magic pill that would make them thin that they would take it" (Taylor & Gailey, 2019, p. 6).…”
Section: )mentioning
confidence: 99%
“…Staying attuned to interviewees’ lived experiences of height as narrated from a first-person perspective, we pursued what one of us has labelled a ‘sociophenomenology of the body’ (Slatman, p. 555),34 and attended to the interviewees’ narrated experiences, paying attention to sociocultural dimensions. We also attended to material dimension of bodily existence and coexistence 56. The interviews focused on participants’ narrations of their everyday experiences of height, including narrations of situations in which they came to think about or note their height.…”
Section: A Sociophenomenology Of the Bodymentioning
confidence: 99%